An analysis of the portrayal of multicultural education in Zimbabwean primary school English textbooks - Mareva, Florence; Mareva, Rugare (IJRDO- Journal of Educational Research, 2016)
Due to the pluralistic nature of the Zimbabwean culture, English language teaching has becomean instrument for effective cultural interaction between different ethnic minority groups.Therefore, content in text books should be representative of all cultures. This paper analyses theextent to which the ethnic minority groups’ cultures are represented in primary school Englishtextbooks. The study posits that ethnic minority groups’ cultures are left out. Through a ContextAnalysis, the study established that ethnic minority groups’ cultures are left out and onlydominant groups’ cultures take a central stage. The study recommends that various ethnicminority groups should be included in the texts to cater for multicultural education